2019
DOI: 10.3389/fnins.2019.01232
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Consequences of Traffic-Related Air Pollution

Abstract: Traffic-related air pollution (TRAP) is a major contributor to global air pollution. The World Health Organization (WHO) has reported that air pollution due to gasoline and diesel emissions from internal combustion engines of automobiles, trucks, locomotives, and ships leads to 800,000 premature deaths annually due to pulmonary, cardiovascular, and neurological complications. It has been observed that individuals living and working in areas of heavy vehicle traffic have high susceptibility to anxiety, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…Regarding the temperature correlation, one reason could be the effect of solar heating, as long as during daytime the dispersion of aerosols is faster. Moreover, the impact of traffic on air pollution, which is a major contributor to local, regional, and global air pollution (Colvile et al 2001 ; Salvi and Salim 2019 ) is well known. For example, Park and colleagues (Park et al 2015 ) found that CO concentration is greatly affected by human activities, especially by the number of cars.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the temperature correlation, one reason could be the effect of solar heating, as long as during daytime the dispersion of aerosols is faster. Moreover, the impact of traffic on air pollution, which is a major contributor to local, regional, and global air pollution (Colvile et al 2001 ; Salvi and Salim 2019 ) is well known. For example, Park and colleagues (Park et al 2015 ) found that CO concentration is greatly affected by human activities, especially by the number of cars.…”
Section: Resultsmentioning
confidence: 99%
“… 2 , 3 Air pollution exposure has consequently been implicated in diverse CNS damage, including vascular damage, chronic neuroinflammation, glial-cell dysregulation, and, in children, global impairments to brain structural integrity, neuron proliferation, and signaling cascades. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), about 90% of people living in urban areas are exposed to air quality levels that exceed the accepted limits for PM 2.5 and PM 10 (10 or 20 μg/m 3 , respectively) [68]. This exposure has been associated with an increase in cardiovascular and respiratory adverse effects [69] and has contributed to decreased cognitive functions, depressive symptoms, and neurodegenerative pathologies [70]. Also, it has generated an economic impact for the countries, represented by an increase in mortality and morbidity, cost overruns for the care of related health events, loss of working hours, school and work absenteeism due to illness or the need to care for a sick person, a decrease in family income and a reduction in productivity [69,71].…”
Section: Discussionmentioning
confidence: 99%